Knowledge, attitudes and practices about goiter among population in Shendi provence. River Nile state of Sudan - Elmanssury, Ahmed Elnadif; Dafaalla, Safa Abdalla (International Journal Of Community Medicine And Public Health, 2017)
Background: Globally, about 2 thousand million people are affected by iodine deficiency. The aim of this study is to Knowledge, attitudes and practices regarding goiter among population in Shendi Provence. River Nile State of Suda. Methods: This study was conducted as a community based descriptive Cross – sectional study. In this study 636 households were included .Questionnaire were used as tools for data collection. The households were selected through a multistage cluster-sampling technique, three cluster stage was used (The locality was divided into four administrative units, All administrative units were divided into cluster villages or block and The required number of households in each village and block was selected by following the systemic random sampling technique) 636 respondents were selected. Results: The study was found that (58.5%) of respondents were recognize goiter disease as an enlargement of thyroid gland. More than sixty (63.4%) were aware of the causes of goiter and its symptoms, (56%) were aware of iodine. More than half of respondents (55.8%) were aware of sources of iodine, (47%) of respondents were aware of foods contain iodine and its types. In addition, study revealed that (41%) of participant were aware of iodized salt. Moreover (48%) of respondents consider that iodized salt is necessary. The results revealed that only 82 (12.9%) were applied Preventive measures. Conclusions: The overall knowledge of respondent regarding goiter were found to be good, they had negative attitude towards goiter and they had proper practice in consumption of food contain.